The effect of oral bisphosphonate therapy on vertebral morphometry and fractures in patients with Duchenne muscular dystrophy and glucocorticoid‐induced osteoporosis. Issue 6 (7th October 2021) - Nasomyont, Nat; Tian, Cuixia; Hornung, Lindsey; Khoury, Jane; Hochwalt, Paul M.; Tilden, Joshua Cole; Wong, Brenda L.; Rutter, Meilan M.
Abstract: Introduction/Aims: Glucocorticoid‐induced osteoporosis with vertebral fractures is frequent in patients with Duchenne muscular dystrophy (DMD). In this study, we evaluated the effects of oral bisphosphonate (BP) therapy on the prevalence and severity of vertebral fractures by vertebral morphometry assessment. Methods: We reviewed the records and radiographs of patients with DMD who had been treated with oral BP (weekly alendronate) and had undergone routine spine radiographic monitoring for glucocorticoid‐induced osteoporosis at Cincinnati Children's Hospital Medical Center between 2010 and 2017. Study outcomes were thoracic and lumbar vertebral fracture prevalence and severity, assessed by Genant semiquantitative grading of vertebral morphometry, for up to 5 years of treatment. Results: Fifty‐two patients (median age, 11.8 years; 88% prepubertal; 31% nonambulatory) had been treated with long‐term glucocorticoids (median duration, 4.7 years at BP start). Most patients (75%) had mild vertebral height loss or fractures (Genant grade = 0 or 1) at baseline. The prevalence of vertebral fractures at each year of treatment was not statistically different from that at baseline ( P = .08‐1.00). Serial radiographs showed no longitudinal change in severity by Genant grade in most vertebrae (64%‐80%). Improvement in vertebral fracture grade was observed in some patients. Discussion: We observed stable prevalence of vertebral fractures and no change in severity by Genant grade in most vertebrae for up to 5 years of treatment. Oral BP may mitigate development or progression of vertebral fractures and be beneficial for secondary prevention of glucocorticoid‐induced osteoporosis in this population.